2009
DOI: 10.4012/dmj.28.743
|View full text |Cite
|
Sign up to set email alerts
|

Dentin bond strength of a new adhesive system containing calcium phosphate experimentally developed for direct pulp capping

Abstract: The purpose of this study was to evaluate the microtensile bond strength (µTBS) to human dentin of an experimental bonding agent containing calcium phosphates experimentally developed for direct pulp capping. Different concentrations of four types of calcium phosphates were added to an experimental bonding monomer, and six experimental bonding agents were thus prepared. Clearfil SE Bond/Bond was used as the control. Flat dentin surfaces of human molars were assigned to the experimental adhesive systems and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 17 publications
2
5
0
Order By: Relevance
“…In the present study, the MTBS values of Groups 1 and 2 -in which 10% NaClO was applied on the dentin surface-were almost equal to that of the positive control group in which NaClO was not applied. The results hereby obtained thus confirmed that dentin surface pretreatment with 10% NaClO did not affect the dentin bond strength of the experimental adhesive system, a finding consistent with that of our previous study 14) .…”
Section: Effect Of Cacl2 Addition On Dentin Bond Strengthsupporting
confidence: 82%
See 3 more Smart Citations
“…In the present study, the MTBS values of Groups 1 and 2 -in which 10% NaClO was applied on the dentin surface-were almost equal to that of the positive control group in which NaClO was not applied. The results hereby obtained thus confirmed that dentin surface pretreatment with 10% NaClO did not affect the dentin bond strength of the experimental adhesive system, a finding consistent with that of our previous study 14) .…”
Section: Effect Of Cacl2 Addition On Dentin Bond Strengthsupporting
confidence: 82%
“…It was thus speculated that pA/pB might have the ability of establishing chemical bonding with superficial dentin matrix, because DMP1 is an acidic protein that binds to calcium ions and initiates mineral deposition. Further on bonding efficacy to dentin, this study showed that the addition of 10 wt% hydroxyapatite to the bonding agent did not significantly reduce the MTBS of the experimental adhesive system to dentin, a finding consistent with that of our previous study 14) .…”
Section: Effect Of Cacl2 Addition On Dentin Bond Strengthsupporting
confidence: 81%
See 2 more Smart Citations
“…In a similar manner, Garcia, Leitune, Samuel, and Collares (2017) did not report any difference between their control and 2% HA groups in their study, which evaluated the immediate bond strength. Shinkai et al (2009) also reported that there was no significant difference in the immediate bond strength values between the 5% HA and the control groups. Although Leitune et al (2013) investigated the immediate bond strength and obtained the best μTBS values for the 2% HA group, they found no statistically significant difference among the 2% and 5% HA groups.…”
Section: Discussionmentioning
confidence: 95%